Partial Purification of Pectinases from Mutants of Aspergillus niger using Moringa oleifera - Kareem, S. O.; Famotemi, A. C.; Oluwafemi, F.; Adewuyi, S. (Al-Hikmah Journal of Pure and Applied Sciences (AJPAS), 2019)
The constant importation of chemicals with scarce foreign currency for purification of pectinase in developing countries has become a major challenge. Pectinase producing A. niger was isolated from soil rich in fruits waste and mutated using NTG (0.3 mg/ml). The pectinase hyper producing wild type and mutants were identified as A. niger isolate SUMS0061, A. niger strain F7-02 and A. niger strain AL-30 using molecular tools. Pectinase from A. niger isolate SUMS0061 produced 1057.14 U/ml, A. niger strain F7-02 produced 2028.57 U/ml and A. niger strain AL-30 had 1242.86 U/ml. Purification with M. oleifera seed powder at optimum concentration (0.75 mg), pH (4-6), temperature (4°C) and contact time (4 hours) produced 10.08-fold for pectinase from isolate SUMS0061, 16.01-fold for pectinase from strain F7-02 and 14.19-fold for pectinase from strain AL-30. A stepwise purification using M. oleifera seed powder and silica gel gave 45.19-fold, 71.20-fold and 63.18-fold for pectinase from isolate SUMS0061, strain F7-02 and strain AL-30 respectively. Molecular weight of each pectinase was 40 kDa. TLC showed that galaturonic acid was the end product of each pectinase hydrolysis. The optimum temperature of pectinase from isolate SUMS0061, strain F7-02 and strain AL-30 were 50 °C, 65 °C and 60 °C respectively. Optimal activity of pectinase from isolate SUMS0061, strain F7-02 and strain AL-30 were at pH 6, 4 and 5 respectively. Each pectinase was stable between pH 3-6. The three pectinases indicated high activities in the presence Ca2+, while Cu2+, Zn2+, Mg2+ and Al3+ led to reduction in pectinase activity.